2023
DOI: 10.3390/ijms24065953
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effect of Pharmaceutical Phytochemicals Targeting the Src Family of Protein Tyrosine Kinases and Aryl Hydrocarbon Receptor on Environmental Stress-Induced Skin Disease

Abstract: The skin protects our body; however, it is directly exposed to the environment and is stimulated by various external factors. Among the various environmental factors that can threaten skin health, the effects of ultraviolet (UV) and particulate matter (PM) are considered the most notable. Repetitive exposure to ultraviolet and particulate matter can cause chronic skin diseases such as skin inflammation, photoaging, and skin cancer. The abnormal activation of the Src family of protein tyrosine kinases (SFKs) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 118 publications
(179 reference statements)
0
6
0
Order By: Relevance
“…We have also demonstrated that Src kinase plays a critical role in ALTOinduced TBK1 phosphorylation and downstream signaling (Fig 4). In the human skin, activated Src is involved in regulating cell adhesion, migration, and proliferation in processes such as wound healing and skin regeneration [49,50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have also demonstrated that Src kinase plays a critical role in ALTOinduced TBK1 phosphorylation and downstream signaling (Fig 4). In the human skin, activated Src is involved in regulating cell adhesion, migration, and proliferation in processes such as wound healing and skin regeneration [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…The pTRIPZ-STING R284S construct was generated in our previous studies [36]. The viral gene constructs used in this study were sourced as follows: pGwf and phGf were from Addgene; pALTOw, pMtw (ST), pWm (VP1), pMono-Zeo, pMono-ADL (LT) and ph2m (VP2) were from the Christopher Buck Laboratory; and the pcDNA4c-57kT construct was generated by first fusing the full 57kT ORF using two-step PCR from pcDNA4c-LT1-817 [51] and then cloning it into the pcDNA4c backbone using the KpnI and XhoI restriction sites.…”
Section: Methodsmentioning
confidence: 99%
“…AhR-modulating drugs can reduce macrophage activation and inflammation in rosacea by targeting the skin’s response to environmental toxins ( 69 ). Tapinarof, an innovative topical treatment acting as an AhR agonist, holds promise in treating rosacea ( 70 ). This molecular mechanism focuses on the AhR, a ligand-activated transcription factor located in the cytoplasm ( 71 ).…”
Section: Progress and Challenges In Macrophage-targeted Therapies For...mentioning
confidence: 99%
“…This molecular mechanism focuses on the AhR, a ligand-activated transcription factor located in the cytoplasm ( 71 ). When tapinarof binds to AhR, it activates the receptor, leading to its translocation into the nucleus of skin cells ( 70 , 72 ). This triggers the transcription of target genes that regulate inflammatory responses and strengthen the skin barrier function ( 73 ).…”
Section: Progress and Challenges In Macrophage-targeted Therapies For...mentioning
confidence: 99%
See 1 more Smart Citation